Demographic Characteristics and Buyers Purchase Decision of Two Wheeler Brands in Bagmati Province, Nepal - Thapa, Makshindra (The Batuk, 2021)
The purpose of this paper is to analyze buyers’ demographic characteristics that influence purchasing decisions of two wheelers brands available in the Nepalese market. The survey study was conducted in the four districts of Bagmati province. Altogether, opinions of 208 respondents were included in the study to express their assertion of two wheeler purchasing decisions. Cross tabulation was done to identify patterns of demographic (categorical) variables and two wheeler brands. The chi-square analysis was done to examine associations between demographic variables and purchase decisions of two wheeler brands. The results of chi-square analysis indicated that buyers’ gender, age, education and occupation have highly significant association with purchase decision. Similarly, income level and marital status are significantly associated with purchase decision. The various categories of demographic characteristics analyzed in the study influence buyer two wheeler brand purchase decisions.